Unlocking academic achievement of nursing master’s students: ethical leadership, teacher-student relationship and growth mindset – a cross-sectional survey study - Duo Zhang; Haoyang Zheng; Ya Zhao; Xiaoxiao Wang; Qi Xiao; Ruiyi Zhao; Lan Wang; Kaili Hu; Zelin Chen; Yanrong Zhou (BMC Medical Education)
Abstract Background Academic achievement is a critical indicator of teaching quality. There has been limited exploration into the mechanisms underlying academic achievements among nursing master’s students. This study investigated the relationship between ethical leadership and academic achievements, focusing on how the teacher-student relationship and growth mindset mediate this relationship. Methods A cross-sectional study was conducted with 262 participants who completed online questionnaires. Data were analyzed using Pearson correlation analysis, structural equation model testing, and deviation correction quantile bootstrap method. Results The average academic achievement score was 51.26 (SD = 5.963). There were significant correlations between ethical leadership, teacher-student relationship, growth mindset, and academic achievement (r = 0.183 to 0.701, P < 0.01). Ethical leadership had a direct positive effect on academic achievement (effect value = 0.224), accounting for 58.49% of the total effect. Mediation analysis revealed that ethical leadership influenced academic achievement through three pathways: ethical leadership → teacher-student relationship → academic achievement (effect value = 0.050), ethical leadership → growth mindset → academic achievement (effect value = 0.080), ethical leadership → teacher-student relationship → growth mindset → academic achievement (effect value = 0.029). Conclusions These findings support our hypothesis that the teacher-student relationship and growth mindset mediate the relationship between ethical leadership and academic achievement. To enhance the academic achievement of nursing master’s students, it is crucial to foster positive teacher-student relationship and promote a growth mindset.